Improving Tourism Destination Management Through Sustainable Tourism Development Model A Case Study on TSR - Sitepu, Edy Sahputra (E-Journal of Tourism; Volume 6 Number 2 (September 2019)DO - 10.24922/eot.v6i2.45746, 2019)
As a priority destination, Lake Toba area should immediately clean up so as not to lag behind compared to other destinations. One important indicator of the good governance of tourism in this priority destination is, when the destination has run the management and development of tourism/destination with the principles of Sustainable Tourism Development (STD). According to Global Sustainable Tourism Council (GSTC) the principles that must be met, among others are; 1) demonstrating effective sustainable management, 2) maximizing social and economic benefit to the local community and minimizing negative impacts; 3) maximizing benefit to cultural heritage and minimizing negative impacts; and 4) maximize benefit to the environtment and minimizing negative impacts in accordance with Permenpar No .14 / 2016. Given the importance of STD implementation in the Lake Toba area, this research tries to assess and influence one of the important destinations in Lake Toba area, namely Taman Simalem Resort (TSR) located right on the edge of Lake Toba, Merek Sub District, Karo District. It is expected that by encouraging TSR in applying STD, TSR can become a local champion and become model of STD application in Toba Lake Area.